Emotional Labour as War Work: Women up close and personal with McIndoe's Guinea Pigs - Byrski, Liz (Routledge, 2012)
In World War II, at a small RAF hospital in the south of England, plastic surgeon Archibald McIndoe carried out groundbreaking surgery on servicemen who had suffered chronically disfiguring facial burns. His regime of treatment and rehabilitation threw out the rule book by encouraging nurses to establish friendships and relationships with the patients. For the nurses this dismantling of the usual boundaries was often difficult to manage. This article examines the nurses' experience and presents a previously undocumented aspect of wartime history which is at odds with public memory.